ANALISIS KESEIMBANGAN NEUROMUSKULAR DAN STRUKTUR ANATOMI KAKI PADA GERAKAN SIKAP LILIN SENAM LANTAI - Helena Selfi Olfia Hosio; Fadjri, Mukharrar; Emayanti Anggraeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Floor gymnastics is one of the basic movement activities in physical education that requires physical ability, coordination, and good technical mastery. One of the fundamental movements in floor gymnastics is the candle position. This study aims to analyze neuromuscular balance and foot anatomy in the candle position in floor gymnastics. This study uses a quantitative approach with a correlational design, which aims to analyze the relationship between neuromuscular balance and foot anatomy in relation to the quality of the candle position in floor gymnastics. The research subjects consisted of students who had basic experience in floor gymnastics. Subject selection was carried out using purposive sampling techniques, with inclusion criteria including: 1. healthy physical condition 2. no lower extremity injuries 3. able to perform the candle position independently. Neuromuscular balance was measured using static balance tests, such as the stork stand test or balance error scoring system (BESS), which have been proven to be valid and reliable in evaluating postural control and neuromuscular stability. The results of this study show a mutually supportive relationship between neuromuscular balance and foot anatomy, where good foot condition improves the effectiveness of proprioceptive sensors and force distribution, thereby facilitating body posture control in inverted positions. Thus, it is confirmed that the synergy between neuromuscular control and foot anatomy is a major factor in the success of the candle pose, making attention to both aspects very important in learning and practicing floor exercises.